2003
DOI: 10.1002/food.200390085
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of aflatoxin B1 in the Egyptain cured meat basterma and control by γ‐irradiation

Abstract: In the present studies trials have been carried out to investigate the occurrence of aflatoxin B1 in the Egyptian cured meat basterma and to control such contamination by gamma-rays. Basterma was prepared from fresh salted meat coated with spice paste and stored at room temperature. The total mould counts of basterma samples varied from 10(3) to 10(6) cfu/g in summer months and from 10(2) to 10(5) cfu/g in winter months. Aspergillus, Penicillium, Mucor, Rhizopus, Fusarium and Cladosporium were the most common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 10 publications
2
17
0
4
Order By: Relevance
“…This can be explained by a highly intense AFB 1 liver metabolism and weak CIT absorption after an oral administration, combined with its quick elimination through urine and faeces (Hirano, Adachi, Bintvihok, Ishibashi, & Kumazawa, 1992;Phillips, Berndt, & Hayes, 1979;Stubblefield, Honstead, & Shotwell, 1991). Moreover, the use of spices contaminated with toxigenic mould strains may also represent a source of secondary mycotoxin contamination of the final product (Refai, Niazi, Aziz, & Khafaga, 2003). The data presented in this study show OTA to be the dominant contaminating mycotoxin.…”
Section: Parametermentioning
confidence: 70%
“…This can be explained by a highly intense AFB 1 liver metabolism and weak CIT absorption after an oral administration, combined with its quick elimination through urine and faeces (Hirano, Adachi, Bintvihok, Ishibashi, & Kumazawa, 1992;Phillips, Berndt, & Hayes, 1979;Stubblefield, Honstead, & Shotwell, 1991). Moreover, the use of spices contaminated with toxigenic mould strains may also represent a source of secondary mycotoxin contamination of the final product (Refai, Niazi, Aziz, & Khafaga, 2003). The data presented in this study show OTA to be the dominant contaminating mycotoxin.…”
Section: Parametermentioning
confidence: 70%
“…So, from these reports and our present results, it appears that fungal strain, condition of storage and irradiation dose aVect mould growth and toxin production (AXatoxin B1, ochratoxin A, zearalenone and fumonisin B1) and further information regarding the ability of gamma radiation to destroy other mycotoxins in food commodities is needed. It has been concluded that gamma-irradiation is an eVective and safe treatment and could be used as a method to control mould growth in food products (Aziz et al, 1997(Aziz et al, , 2005Gharib & Aziz, 1995;Refai et al, 2003). It is assumed that there would be no remaining mycotoxins in food commodities irradiated with dose up to 10-20 kGy.…”
Section: Distribution Of Fusarium Moulds and Fumonisin B 1 In Diverenmentioning
confidence: 99%
“…Various methods of preservation have been applied to arrest growth of moulds in foods such as fumigation and heat treatment, but none of these methods oVers complete control of toxigenic moulds. Ionizing radiation is one of the methods applied to decontaminate pathogenic microorganisms in diVerent food commodities (Aziz & Mahrous, 2004;Aziz & Moussa, 2002Mahrous, Aziz, & Shahin, 2003;Refai, Niazi, Aziz, & Khafaga, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Em relação à aplicação da irradiação gama ( 60 Co) em alimentos observa-se um grande número de publicações (AHMAD et al, 2002;AQUINO, 2003;AZIZ & MOUSSA, 2002;AZIZ & YOUSSEF, 2002;FARKAS, 2006;FOONG et al, 2004;PRADO et al, 2005aPRADO et al, ,b, 2003PRADO et al, , 2006REFAI et al, 2003). Entretanto, poucos são os trabalhos que descrevem a utilização de 60 Co em plantas medicinais e produtos fitoterápicos.…”
Section: Resultsunclassified